Relation of polar auroral arcs to magnetotail twisting and IMF rotation: a systematic MHD simulation study - A. Kullen; P. Janhunen (Annales Geophysicae, 2004)
We investigate with the help of a magnetohydrodynamic (MHD) model how the large-scale topology of the magnetosphere develops for a constant interplanetary magnetic field (IMF) with different IMF clock angles and for an IMF By sign change during northward IMF. A detailed examination of the topological changes in the tail and the ionosphere for different IMF conditions shows a good agreement with observational results.